The Relationship Of Stress Level and Eating Patterns With Nutritional Status In Class X Adolescents At SMA Negeri 1 Surabaya Post Implementation Of The Independent Curriculum - Rachmalia Azzahrah Chairunnisa; Nur Hatijah; Taufiqurrahman; Ani Intiyati; Santhra Segaran Balan (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Indonesian adolescents are at risk of stress due to the implementation of the Merdeka Curriculum. An unbalanced diet is also a common problem among adolescents, affecting their nutritional status and health. To determine the relationship between stress levels and dietary patterns with nutritional status in grade X adolescents at SMA Negeri 1 Surabaya after the implementation of the Merdeka Curriculum. This study is included in observational analytical research, with survey and questionnaire interview. data was conducted through filling out consent forms by respondents and anthropometric measurements and questionnaire interviews with grade X students at SMAN 1 Surabaya who have agreed to be respondents. The study shows that nutritional status is not related to a person's stress level, that stress does not cause a person's nutritional status to be problematic. However, there is a relationship between diet and status. Based on the results, there is no relationship between stress levels and nutritional status, while diet and nutritional status show a relationship in grade X adolescents at SMAN 1 Surabaya after the implementation of the Merdeka Curriculum. It is recommended that both students and schools emphasize balanced diets tailored to nutritional needs and foster stress management practices both at school and home.